2014
DOI: 10.1111/jon.12079
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nerve Ultrasound, Electrophysiological and Clinical Findings in Chronic Inflammatory Demyelinating Polyneuropathy

Abstract: CIDP seems to show inhomogenous CSA enlargement in brachial plexus and peripheral nerves, with weak correlation to electrophysiological findings. Neither nerve sonography nor electrophysiology correlated with functional disability in CIDP patients. Multicenter, prospective studies are required to proof the applicability and diagnostic values of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 43 publications
(49 reference statements)
9
83
2
6
Order By: Relevance
“…[16][17][18][19] In further ultrasound studies of CIDP patients, diffuse nerve enlargements could be demonstrated. 20 These findings seem to correlate with the disease duration, but don't seem to show any significant correlation with functional disability or NCS findings. [21][22][23] Another important aspect in the field of sonography in CIDP, is the possible use of this method for identifying nerve conduction blocks.…”
Section: Ultrasound Findings In Chronic Inflammatory Demyelinating Pomentioning
confidence: 83%
“…[16][17][18][19] In further ultrasound studies of CIDP patients, diffuse nerve enlargements could be demonstrated. 20 These findings seem to correlate with the disease duration, but don't seem to show any significant correlation with functional disability or NCS findings. [21][22][23] Another important aspect in the field of sonography in CIDP, is the possible use of this method for identifying nerve conduction blocks.…”
Section: Ultrasound Findings In Chronic Inflammatory Demyelinating Pomentioning
confidence: 83%
“…В ряде исследований по-казано увеличение ППС нервов при ХВДП [9,10,12], в основе которого лежат классические гистологические изменения нервов по типу «луковичных головок», как следствие чередующихся процессов демиелинизации/ ремиелинизации. Увеличение ППС определяется как в проксимальных, так и в дистальных участках нервов, что свидетельствует об относительной генерализации иммуноопосредованной демиелинизации [7,10,15].…”
Section: том 6 Volunclassified
“…В отличие от ХВДП, при которой нейро-физиологические отклонения в целом коррелируют с данными сонографического исследования нервов, попытки корреляции блока проведения и скорости распространения возбуждения при ММН с увеличе-нием ППС не увенчались успехом [6,7,15]. Более того, ЭМГ-и УЗ-изменения при ММН не коррелируют с двигательным дефицитом [3], что значительно осложняет диагностику, дифференциальную диагно-стику и трактовку получаемых результатов.…”
Section: том 6 Volunclassified
“…[37][38][39][40][41][42] In addition, two studies reported increased values of the intranerve CSA variability in several peripheral nerves, highlighting the focal pattern of CSA enlargement occurring in CIDP. 41,42 Although these findings are promising for the imaging of the structural affection of the nerves, they add little, if any, in the differentiation of subacute CIDP from AIDP.…”
Section: -36mentioning
confidence: 99%
“…43 The idea behind the development of the concrete ultrasound score was based on the statistical comparison of the distribution pattern of pathological ultrasound findings between these two polyradiculoneuropathies. 42,44 The newly established 'Bochum Ultrasound Score' (BUS) includes the measurement of the cross-sectional area of (a) the ulnar nerve in Guyon's canal, (b) the ulnar nerve in upper arm, (c) the radial nerve in spiral groove and (d) the sural nerve between the lateral and medial head of the gastrocnemius muscle (see Figure 1). The new scoring system includes two rules: (1) the patient receives 1 point for each of the aforementioned anatomic sites where he or she shows pathological cross-sectional area enlargement compared with the reference values, 43 and (2) if the patient shows a pathological crosssectional area nerve enlargement of the concrete nerve on both sides of the body, he or she also receives only 1 point.…”
Section: -36mentioning
confidence: 99%